2018
DOI: 10.1016/j.artd.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Fracture of an S-ROM stem at the sleeve-stem junction

Abstract: Fracture of a well-ingrown femoral component is a rare and often challenging complication. Modular junctions and sleeve interfaces have been identified as one potential point of weakness with corrosion and fretting being contributing factors to ultimate femoral component fracture. Stem fractures at the sleeve interface were reported occasionally for the proximal ingrowth modular Emperion System (Smith and Nephew, Memphis, TN). However, this failure mechanism has been reported infrequently, often associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…It has also been reported that the combined prosthesis with adjustable anterior inclination (S -ROM prosthesis) can be used to adjust the size of the anterior inclination of the femoral neck by means of osteotomy under the femoral trochanter [32,33]. At the same time, there are also reports that the modular femur component may cause fracture risk at the link of the prosthesis due to fretting, corrosion and other reasons [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that the combined prosthesis with adjustable anterior inclination (S -ROM prosthesis) can be used to adjust the size of the anterior inclination of the femoral neck by means of osteotomy under the femoral trochanter [32,33]. At the same time, there are also reports that the modular femur component may cause fracture risk at the link of the prosthesis due to fretting, corrosion and other reasons [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…In this case report, we discuss one of four reported cases of the fracture of a spline of the S-ROM prosthesis, which was fully discovered during stem extraction. As there are only 18 known reports (including the present study) of fractures of the S-ROM prosthesis at different prosthetic locations, and at different time points postoperatively [ 3 , 4 , 6 - 12 ], it is important to document trends in implant survivorship (Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…At these interfaces between modular components, corrosion, metal ion generation, and fretting may occur [ 14 , 15 ]. This corrosion concentrated in the neck/sleeve region can reduce prosthesis integrity, especially when coupled with small-diameter diaphyseal stems and large neck offsets in obese patients, resulting in “fatigue fracture” due to massive bending forces on the neck-sleeve or sleeve-stem interface [ 6 ]. Approximately 14 cases of S-ROM fractures at the modular neck due to this “fatigue fracture” mechanism exist in the literature [ 6 - 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations